Harnessing the Power of Patient-Generated Data - Choe, Eun Kyoung; Lee, Bongshin; Andersen, Tariq O.; Wilcox, Lauren; Fitzpatrick, Geraldine (Pervasive Computing, 2018)
The authors report on the PervasiveHealth 2017 workshop, “Leveraging Patient-Generated Data (PGD) for Collaborative Decision Making in Healthcare.” They discuss characteristics of PGD, followed by scenarios demonstrating the data-sharing practice among patients, clinicians, and caregivers. The authors also highlight current challenges and opportunities, and outline a future research agenda to envision ways to harness the power of PGD.